Qualifications and functions of physicians, dentists and nurses in the city of Manila public schools and their implications for health education - Cortes, Rosario (Twano) 1937- (1968)
This study analyzed the educational qualifications and functions of school physicians, dentists and nurses, and determined their implications on health education. The study shows that majority of the school physicians, dentists and nurses in the city of Manila public schools have had little preparation in the field of school health education and have taken no formal course in the same field. Majority have not had additional training beyond their respective degrees - Doctor of Medicine, Doctor of Medical Dentistry, and Graduate Nurse, as the case may be.